Evaluation of a 3D-Printed Exoskeleton for Reducing Lower Back Muscle Load in Tomato Greenhouse Applications - Le, Dang Khanh Linh (EAI Endorsed Transactions on Sustainable Manufacturing and Renewable Energy, 2025)
Lifting and carrying tasks are known to increase the risk of work-related musculoskeletal disorders, particularly in the lower back region. This study aims to evaluate the effectiveness of a 3D-printed prototyping exoskeleton (RPE) in reducing the strain on lower back muscles during the transport of fruit boxes in a tomato greenhouse. A 3D-printed exoskeleton was designed and tested, with participants performing tasks such as lifting, carrying, and lowering heavy objects on tomato farms. The evaluation involved comparing muscle activity with and without the exoskeleton intervention. Muscle activity data were collected from 15 participants, focusing on the erector spinae (ES), latissimus dorsi (LD), anterior deltoid (AD), and medial deltoid (MD) muscles. The results demonstrated that using the exoskeleton significantly reduced the load on back muscles by 55.65% to 63.55% during lifting. Additionally, during carrying tasks, the exoskeleton reduced the load on the anterior deltoid muscle by 7.00% to 8.61%. The RPE also effectively decreased rectus femoris activity during dynamic lifting and carrying tasks, potentially alleviating pain and discomfort and reducing the risk of developing back-related disorders.